2011
DOI: 10.1021/ie2010274
|View full text |Cite
|
Sign up to set email alerts
|

How Chemistry, Nanoscale Roughness, and the Direction of Heat Flow Affect Thermal Conductance of Solid–Water Interfaces

Abstract: We quantify the Kapitza thermal conductance of solid–liquid interfaces between self-assembled monolayers (SAMs) and liquid water using nonequilibrium molecular dynamics simulations. We focus on understanding how surface chemistry, nanoscale roughness, and the direction of heat flow affect interfacial thermal conductance. In agreement with calculations by Shenogina et al. (Phys. Rev. Lett., 2009, 102, 156101) for SAMs with homogeneous headgroup chemistries, we find that for mixed −CF3/–OH SAMs, thermal conducta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 44 publications
4
82
1
Order By: Relevance
“…Barrat and Chiaruttini 31 used MD simulations to show that the solid/liquid thermal boundary conductance increases with an increase in the wetting of a surface; Murad and Puri 32 and Xue et al 33 found this same dependence. Shenogina et al 34 took this step further and demonstrated that h K across a solid/liquid interface varies linearly with work of adhesion, consistent with recent experimental work of Harikrishna et al 19 Acharya et al 35 showed that in addition to bonding considerations, h K at solid/liquid interfaces is also intimately coupled to chemical heterogeneity, roughness, and contact area.…”
Section: Background: Solid/liquid Thermal Couplingmentioning
confidence: 53%
“…Barrat and Chiaruttini 31 used MD simulations to show that the solid/liquid thermal boundary conductance increases with an increase in the wetting of a surface; Murad and Puri 32 and Xue et al 33 found this same dependence. Shenogina et al 34 took this step further and demonstrated that h K across a solid/liquid interface varies linearly with work of adhesion, consistent with recent experimental work of Harikrishna et al 19 Acharya et al 35 showed that in addition to bonding considerations, h K at solid/liquid interfaces is also intimately coupled to chemical heterogeneity, roughness, and contact area.…”
Section: Background: Solid/liquid Thermal Couplingmentioning
confidence: 53%
“…Flat SAMs provide excellent systems to analyze the effects of chemical patterns on hydrophobicity without being encumbered by the effects of surface topography (40,54,55). We study SAM surfaces with n hydrophilic sites (-OH head groups) in a background of hydrophobic sites (-CH3 head groups) (see SI Appendix for details).…”
Section: Surfaces With the Same Chemistry But Different Patterns Can mentioning
confidence: 99%
“…The interaction strength α has been discovered to have a significant effect on heat transport in solid-liquid systems [1][2][3][4][5]9]. In this section, we set M S1 = 0.5M L , M S2 = 2.0M L , and vary α in the range of 0.1 to 5.0.…”
Section: Effect Of Interaction Strength Between Liquid and Solidmentioning
confidence: 99%
“…Then, the solid surface structure effects such as surface functionalization, roughness, composition, etc. were also considered [8,9]. Astoundingly, the interface thermal conductance was proportional to the magnitude of the surface roughness.…”
Section: Introductionmentioning
confidence: 99%